The European Border and Coast Guard: A New Model Built on an Old Logic - Philippe De Bruycker (European Papers, 2016)
(Series Information) European Papers - A Journal on Law and Integration, 2016 1(2), 559-569 | On the Agenda | (Table of Contents) I. Introduction. - II. A new model? Hierarchy within an intergovernmental network. - III. An old logic! Prioritising responsibility over solidarity. - IV. Conclusions. | (Abstract) Due to the refugee crisis, the Proposal made by the Commission in December 2015 to create a European Border and Coast Guard (EBCG) will soon become legislation adopted in record time with a large consensus. Wrongly considered as an ambitious solution, it is based on highly questionable principles. Firstly, it transforms the EBCG Agency into the Chief Executive Officer of the Member States authorities in charge of border controls. This is a welcome new model because of the current powerlessness of Frontex, but it does not guarantee the independence towards Member States of this new Agency that will remain intergovernmental. In reality, the Proposal does not create in the true sense an EBGC that will be nothing more than a legal fiction while its misleading title will keep going the confusion between the numerous concepts used in the European borders policy. Secondly, although the Commission pretends to share border controls between the EU and its Member States, the latter will remain responsible for their implementation which is in contradiction with the principle of solidarity, with the consequence that the funding of the European borders policy will remain an unsolved problem. Actually, the Proposal follows the old logic of a supposed principle of responsibility and gives it the priority over the necessary solidarity in violation of the Treaty and in contradiction with the new orientation given by the Commission to the asylum policy. The EBGC could be a short-term solution to the situation at the Greek borders, but it will not solve the structural problem of border controls in the EU that requires a centralised agency for which there is no legal basis in the Treaty.